EPISTEMOLOGICAL DIALECTICS AND THE INTEGRATION OF KNOWLEDGE: FROM A VALUE CRISIS TO A GLOBAL CIVILIZATION - Fadli Ramadhanul Aflah; Eva Dewi; Rivaldiansolih Lubis (SOSIOEDUKASI, 2025)
The value crisis accompanying the development of modern science indicates a disorientation between technological progress and human moral quality. This article aims to examine the dialectics of epistemology and the concept of knowledge integration as a conceptual solution to address this issue. The research method employed is a literature study with a descriptive,analytical approach, using critical analysis of national and international journal articles published in the last five years. The findings show that Western epistemology, based on rationalism and empiricism, tends to produce secular knowledge, while Islamic epistemology places revelation, reason, and experience within an integral framework. The dialectics between the two gives rise to the idea of integration,interconnection, which is more adaptive to the context of higher education in Indonesia. The implementation of knowledge integration still faces structural and cultural challenges, yet conceptually it offers an alternative paradigm to build a more just, humanistic, and sustainable global civilization. The study concludes that epistemological reconstruction through knowledge integration is not only an academic necessity but also a civilizational project urgently needed to overcome the global value crisis.